Seed production of field crops in India: Quality assurance, status, impact and way forward - CHAUHAN, J S; PRASAD, S RAJENDRA; PAL, SATINDER; CHOUDHURY, P R; BHASKAR, K UDAYA (The Indian Journal of Agricultural Sciences, 2016)
Of the several factors vital for enhancing production and productivity of the crops, seed is a critical input for long- term sustained growth of agriculture. A robust seed system is the first and foremost step towards food security of the country and acts as driver of growth in agriculture. From a predominantly public sector in the 1960’s, the Indian seed sector has evolved gradually into a multi-faceted industry with involvement of large number of private firms and increasing emphasis on research and development activities. The present paper reviews the evolution of seed sector in India, quality assurance regulations, international seed testing and certification, development of varieties and their induction in the seed chain, present status of breeder, foundation and quality/certified seed production. The paper also discusses the varietal scenario in the seed chain during 2014-15, demand and availability of seed and contributions of public and private seed sector. On quality seed front, production of 3.52 MT (2014-15), more than requirement was made possible due to synergistic efforts of public and private sectors in Indian seed domain. Analysis of Indian seed production scenario revealed that seed production has shown compound growth rate of 16-17 %, which is an encouraging positive sign and Indian seed industry is vibrant and strong enough to make its presence felt in global seed domain and India is poised for up-scaling its current position, 6th with US 2 billion, in international seed market valued at US 45 billion. Indian seed sector managed this growth due to proactive policy support and seed markets such as Bt cotton, hybrids of vegetables, rice and maize especially, single cross hybrids. An attempt has also been made in the present study to analyze the impact of quality seed on Indian agriculture, potential for seed export, way forward and strategies for meeting the emerging challenges in the seed sector for enhancing seed replacement rate, varietal replacement rate and making quality seed available to the farmers at affordable prices for up-scaling and sustaining high yield in field crops.